Cross-sectional observational assessment of quality of newborn care immediately after birth in health facilities across six sub-Saharan African countries. Issue 3 (27th March 2017) - de Graft-Johnson, Joseph; Vesel, Linda; Rosen, Heather E; Rawlins, Barbara; Abwao, Stella; Mazia, Goldy; Bozsa, Robert; Mwebesa, Winifrede; Khadka, Neena; Kamunya, Rosemary; Getachew, Ashebir; Tibaijuka, Gaudiosa; et al.
Abstract : Objective: To present information on the quality of newborn care services and health facility readiness to provide newborn care in 6 African countries, and to advocate for the improvement of providers' essential newborn care knowledge and skills. Design: Cross-sectional observational health facility assessment. Setting: Ethiopia, Kenya, Madagascar, Mozambique, Rwanda and Tanzania. Participants: Health workers in 643 facilities. 1016 health workers were interviewed, and 2377 babies were observed in the facilities surveyed. Main outcome measures: Indicators of quality of newborn care included (1) provision of immediate essential newborn care: thermal care, hygienic cord care, and early and exclusive initiation of breast feeding; (2) actual and simulated resuscitation of asphyxiated newborn infants; and (3) knowledge of health workers on essential newborn care, including resuscitation. Results: Sterile or clean cord cutting instruments, suction devices, and tables or firm surfaces for resuscitation were commonly available. 80% of newborns were immediately dried after birth and received clean cord care in most of the studied facilities. In all countries assessed, major deficiencies exist for essential newborn care supplies and equipment, as well as for health worker knowledge and performance of key routine newborn care practices, particularly for immediate skin-to-skin contact and breastfeeding initiation. Of newborns who did not cry at birth, 89% either recovered on their own or through active steps taken by the provider through resuscitation with initial stimulation and/or ventilation. 11% of newborns died. Assessment of simulated resuscitation using a NeoNatalie anatomic model showed that less than a third of providers were able to demonstrate ventilation skills correctly. Conclusions: The findings shared in this paper call attention to the critical need to improve health facility readiness to provide quality newborn care services and to ensure that service providers have the necessary equipment, supplies, knowledge and skills that are critical to save newborn lives.